Can we avoid digital structural violence in future learning systems?. Issue 1 (2nd January 2020) - Winters, Niall; Eynon, Rebecca; Geniets, Anne; Robson, James; Kahn, Ken
ABSTRACT: This paper introduces the concept of digital structural violence and examines the negative role it could have in future learning systems. To address it, we propose a new interdisciplinary research agenda at the intersection of three current but disparate lines of work that: Use the concept of epistemic privilege to theorise the inclusion of marginalised learners in the design of learning systems, and utilise participatory action research and emancipatory methodologies to pragmatically ensure this happens; Support young learners and teachers to understand and build their own artificial intelligence algorithms; Develop sustainable interdisciplinary links with computer science to address digital structural violence at the algorithmic level and to make its societal implications and underlying processes more widely understood, especially by teachers. Taken together, these provide for a material form of resistance to digital structural violence and a theoretically and methodologically coherent future research agenda for building just learning systems.